Hubungan Asupan Energi Dan Kepatuhan Komsumsi Tablet Fe Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Kampa Tahun 2023 - Ridwana, Renty; Harahap, Dewi Anggriani; Lubis, Dumasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Anemia is more common in women than men. Kampar Regency is one of the districts with an increase in the prevalence of central obesity. The aim of this research is to determine the relationship between energy intake and adherence to consuming fe tablets with the incidence of anemia in pregnant women in the Kampa Health Center working area in 2023. This type of research is quantitative with a cross sectional design. The population in this study were all pregnant women in encroachment villages in the working area of ​​the Kampa Health Center in 2023, totaling 111 people with a total sampling technique of 89 people. The data collection technique used a 2×24 hour food recall questionnaire and 1×24 hour physical activity, measurement of weight, height and abdominal circumference. The results of univariate analysis showed that 75 people (63.0%) had more energy intake, 70 respondents with moderate physical activity (58.8%), 91 people (76.5%) had central obesity. The results of bivariate analysis of energy intake using the Chi Square test showed that there was a relationship between energy intake (p=0.00) and the incidence of anemia and there was a relationship between adherence to consuming Fe tablets (p=0.00) and the incidence of anemia